PENDUGAAN FUNGSI KEUNTUNGAN DAN RISIKO USAHATANI SAWI PAHIT (Brasischa juncea) DI DESA SAMBIREJO KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Utama, Satria Putra; Badrudin, Redy; Rien, Merry (Jurnal AGRISEP, 2006)
This research was aimed to estimate of profit,  know determinant factors of profit, and measure farm risk level. The research location was determined purposive in Sambirejo village, Selupu Rejang district of Rejang Lebong region. 34 sample was using by simple random sampling method. Summed uply sample counted 34 responder people. Data used were primary and secondary data then analysed qualitative and also quantitative. The analyzed method that used to see the stock of production factors used descriptive method. Analyzed data to profit that was total of revenue less the total cost. Profit function of UOP Cobb Douglas used to know influence of production factors to profit. Coefficient variation used to measure farm risk level. Result of this research showed that, the average of farmer’s profit from the bitter mustard farming in sambirejo village, rejang lebong region on planting season of May/Juni are Rp.914.382,33/farm or Rp.4.747.964,79/Ha, and planting season of Feb/Maret are Rp.1.025.509,72/farm or Rp.6.698.378,53/Ha. Variable which influenced negatively and  significantly  on profit function of bitter mustard farming in sambirejo village, Selupu Rejang district of Rejang Lebong region on planting season of Feb/Maret and May/Juni are the land fare (X8*), production amount (X9*) and dummy variable (season plant). whereas, variables which influenced negatively and unsignificantly are the price of seed (X1*), the price of urea (X2*), but the price of dursban (X5*) influence positively and also has tendency to increase the profit of bitter mustard profit. The lowest value of risk (CV) or the level of risk on bitter mustard farming at Feb Maret is 0,50 or 50 percent with the bottom limit of profit (L) as Rp.-32.654,07/Ha. And at May/Juni is 0,57 or 57 percent with the bottom limit of profit as Rp.-691.212,19/Ha.Key word : Profit function, Farming risk